The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jnucmat.2013.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of molten W exposed to high heat flux helium neutral beams

Abstract: High heat flux tests with central heat flux of 10.5 MW/m 2 using helium neutral beams have been carried out on rolled tungsten. The energy of helium particles is 33 keV and the particle flux is 2×10 21 m -2 s -1 . An 80×65×3 mm 3 rolled tungsten plate is firstly exposed to a 4.6 s pulse resulting in partially molten surfaces. Thereafter the tungsten plate is irradiated by several helium pulses with fluences of 1.2-2.5×10 22 /m 2 and peak temperatures from 1450 to 2590 °C . The experiments show that: (1) helium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…1 summarizes the results reported in Ref. [2], [5] and [7], and shows the observed relationship between surface modification, fluence and peak surface temperature. The mechanism for the formation of these surface morphologies is, however, not fully understood, especially the effects of temperature dependence.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…1 summarizes the results reported in Ref. [2], [5] and [7], and shows the observed relationship between surface modification, fluence and peak surface temperature. The mechanism for the formation of these surface morphologies is, however, not fully understood, especially the effects of temperature dependence.…”
Section: Introductionmentioning
confidence: 78%
“…The mechanism for the formation of these surface morphologies is, however, not fully understood, especially the effects of temperature dependence. In addition, some studies have found an orientation dependence for He-induced damage [3,5,8]. This is interesting as it may provide a way to optimize the plasma facing material by control of the crystallographic texture.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The saturation of helium atoms leads to the formation of bubbles as well. Depending on the irradiation conditions, bubbles ranging from several tens of nanometers up to micron in size can develop in the material [9,10]. Moreover, with increasing temperature (above 700°C) and fl uence approximately 10 25 m -2 a nanostructure called helium/tungsten 'fuzz' starts to develop [11].…”
Section: Introductionmentioning
confidence: 99%